JARANAN KEDIRI: HEGEMONI DAN REPRESENTASI IDENTITAS - Dhany Oktaviany; Muh. Rosyid Ridlo (Journal of Development and Social Change, 2018)
Abstract : Disscussion about jaranan art performance is never going to stand as an art alone. Jaranan art performance is part of socio-histories in Kediri’s society. There are several aims of this research such as, to know the identity representation of jaranan’s community in Kediri, to explain the rulling class’s hegemony and to explain the representation politic of jaranan Kediri’s community. Antonio Gramsci’s Hegemony theory dan Stuart Hall’s Representation theory are being used in this research. This research is located in Kota subdistict of Kediri city, East Java. This qualitative research used the etnography approach by James Spradley. Purposive sampling is being used as sampling technique in this research. Interview, focus group discussion (FGD) and documentation are being used as data collecting technique. The analysis technique is using theme analysis by Spradley. The result form this research is that, in order to face the power relation, jaranan Kediri’s community form several kind of identity representation. That identity representation such as, (1) Festival Jaranan; (2) tanggapan Jaranan; (3) dance-drama Jaranan for religious event and; (4) dance-drama lakon Dewi Sanggalangit. Jaranan Kediri isnt stop being just an art in the cultural area of Kediri’s society, but Jaranan aslo become an area of power domination in the hegemony system of rulling class. Jaranan stood as a social-cultural power in the society, make it’s hard to slipped away from the hegemony hand. There are two hegemonic alliance in the rulling class level, there are government/Islam religion alliance and economi/local elit alliance. Govenment/Islam religion using cultural-leadership based on Islam ideology and the eceonomy/local elit using fromal economy ideology. Ruling class is side on hegemony block, whereas the jaranan community stood as counter hegemony block. the hegemony fall to descedent hegemony rank. Representation politic are beling held to face the three sector which is, government, religion and economy.Keywords :Jaranan, hegemony, representation, identity, politics, government, religion, economy.Abstrak : Membicarakan kesenian jaranan tidak akan pernah bisa dibahas dalam satu topik tunggal berupa seni. Kesenian jaranan merupakan bagian integral dan sosiohistoris masyarakat kota Kediri. Penelitian ini bertujuan untuk mengetahui representasi identitas komunitas kesenian jaranan Kediri, menjelaskan hegemoni rulling class dan menjelaskan politik representasi idetitas dari komunitas kesenian jaranan kota Kediri. Teori yang digunakan adalah teori hegemoni yang dikemukakan oleh Antonio Gramsci dan teori representasi oleh Stuart Hall. Penelitian ini mengambil lokasi di Kecamatan Kota, Kota Kediri, Jawa Timur. Peneltitian kualitatif ini menggunakan metode penelitian yakni, studi etnografi James Spradley. Teknik pengambilan sampel data adalah dengan Purposive sampling. Teknik pengambilan data adalah dengan wawancara, FGD dan dokumentasi. Teknik analisis yang digunakan adalah teknik analisis tema yang diadaptasi dari etnografi James P. Spradley. Hasil penelitian komunitas kesenian jaranan di kota Kediri. Dalam menghadapi relasi kuasa pemerintah, agama dan pasar tersebut, komunitas kesenian jaranan membentuk empat representasi identitas yakni; (1) Jaranan festival; (2) jaranan tanggapan; (3) Jaranan Sendratari untuk acara Agama Islam dan; (4) Jaranan Sendratari lakon Dewi Sanggalangit.Kesenian jaranan tidak berakhir hanya menjadi suatu kesenian dalam aspek budaya saja namun jaranan Kediri mejadi arena dominasi kekuasaan dari rulling class. Jaranan di Kota Kediri hadir sebagai suatu kekuatan sosio-budaya rakyat, yang tak luput dari proses hegemoni oleh rulling class tersebut. Terdapat dua aliansi kelompok hegemonik yakni pemeritah/agama dan ekonomi/elit lokal. pemerintah/agama menggunakan kepemimpinan kultural dasar ideologis agama, sementara ekonomi/elit lokal menggunakan ideologi ekonomi formal. Blok hegemoni oleh rulling class dan counter hegemoni oleh komunitas jaranan. Tingkatan hegemoni yang tercipta adalah decedent hegemony. Politik representasi yang dilakukan menyasar pada tiga bidang yakni, pemerintah, agama dan pasar.Kata kunci: Jaranan, hegemoni, representasi, identitas, politik, pemerintah, agama, pasar.